Skabt i Guds billede. En lidet kendt udredning af Grundtvig fra 1814 - Grundtvig, N. F. S. (Grundtvig-studier, 1986)
Created in the Image of Goda little-known account of Grundtvig from 1814 The creation of man in the image of God means according to Grundtvig that man is created with the purpose of resembling the Trinity - Father, Son and Holy Spirit. Man is therefore tripartite, comprising body, soul and spirit, equipped to feel, imagine, and apprehend. As Father, God cannot be truly imagined, since our images are limited by time and space. When man nevertheless sets out to imagine God, it is as Creator, according to the Bible as “the living word” – as the Son. The Holy Spirit then becomes the power that unites the Father and the Son. Grundtvig believes that man must be created with free will, “for otherwise there was something that did not obey Him”, that is, God - namely the human will.However, Grundtvig does not envisage the newly-created man as a perfect image of God, but rather as a healthy new-born baby is “fully-developed” - with the potential to become the perfect image of God. The Fall breaks off this development, occurring as it did because man abused his reason by doubting the truth of God’s word: “of the tree of knowledge of good and evil, thou shalt not eat of it,” for “thou shalt surely die.” Instead man believed the devil’s words, which were lies, and let his reason serve his desire. If we doubt that we participate in this sin, we will be convinced “when we realise how little abhorrence we have of such a fall.” This was pride, and this was how we lost our immediate communion with God.This account is found in the first volume of Grundtvig’s second World Chronicle, published in 1814. Only the one volume was published; it has never been reprinted, and is therefore little-known.